Efficacy, tolerability, and retention of fenfluramine for the treatment of seizures in patients with Dravet syndrome: Compassionate use program in Germany - Strzelczyk, Adam; Pringsheim, Milka; Mayer, Thomas; Polster, Tilman; Klotz, Kerstin A.; Muhle, Hiltrud; Alber, Michael; Trollmann, Regina; Spors, Hartwig; Kluger, Gerhard; Kurlemann, Gerhard; Schubert-Bast, Susanne (Epilepsia, 2021)
Objective: Dravet syndrome (DS) is a rare but severe drug-resistant epilepsy. Before the approval of fenfluramine (FFA) for the treatment of seizures in DS, patients in Germany could receive treatment under a compassionate use program (CUP). Methods: We conducted a multicenter, retrospective, observational study to describe the efficacy, tolerability, and retention of FFA within the CUP. Patients received add-on therapy with oral FFA gradually titrated to a target dose between.13 and.7 mg/kg/day. Results: Overall, 78 patients with DS (median age = 8.0 years, range = 2.1–46.0; 53% female, median concomitant antiseizure medications [ASMs] = 3) were treated with FFA for a median duration of 255.5 days (range = 31–572). Responder rates (a ≥50% reduction; n = 78) and seizure-freedom rates at 3 months were 68% and 14% for total seizures, respectively, and 67% and 23% for generalized tonic–clonic seizures. Responder rates were consistent at 6 and 12 months (n = 66 and n = 43, respectively). Median seizure days per month significantly decreased from 10.0 (range =.5–30) to 3.0 (range = 0–30) in the 3-month period before and after FFA treatment (p <.001). Significantly fewer patients reported at least one episode of status epilepticus (28% vs. 14% patients before and after FFA initiation, p =.005). During FFA treatment, 35 (45%) patients were able to discontinue a concomitant ASM. At the last follow-up date, 66 (85%) patients remained on treatment with FFA. The most common adverse events were somnolence (36%), decreased appetite (22%), and ataxia (8%). Forty-eight (62%) patients were reported as having a meaningful global clinical improvement. Significance: In a large cohort of patients, FFA demonstrated efficacy across a range of outcomes including clinically significant reductions in convulsive seizures, and was well tolerated, providing valuable information for real-world practice.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Clinical Global Impression of Change; convulsive seizures; Dravet syndrome; fenfluramine; real-world; status epilepticus